Tourism Management In Increasing Regional Genuine Income In The Province Of The Special Capital Region Of Jakarta (Study During The Covid-19 Pandemic) - Risnawati Risnawati; Hadi Prabowo; Hyronimus Rowa (Lembaga Riset dan Inovasi Al-Matani, 2023)
The main purpose of this research is to determine the effect of quality of service, brand image, customer experience and customer satisfication on consumer loyalty. Consumer loyalty is consumer loyalty to the company, brand or product. Object of this research is customers who bought at PT. Kertajaya Utama Pekanbaru. Sampel used in this research is 100 customers who bought at PT Kertajaya Utama Pekanbaru. Sampling method used is purposive sampling. Methods of data analysis is multiple linear regression with SPSS. Independent variable is quality of service, brand image, customer experience and customer satisfication. The dependent variable is onsumer loyalty. This research adduce that quality of service, brand image, customer experience and customer satisfication has positive significant effect on purchasing decisions.